Structural holes and brokering in triadic supply networks in industrial digital service innovations - Momeni, Beheshte; Kohtamäki, Marko (Emerald, 2026)
Purpose This study explores how industrial firms structure their relationships with technology providers and customers in digital service innovations (DSIs) – the use of digital technologies to create new value-added services. DSIs challenge supply network structures by reshaping roles and creating new dependencies. Therefore, understanding these changes is critical as they affect innovation outcomes, control over customer access, technology integration, and strategic positioning. Drawing on structural holes and brokerage, the study examines how industrial firms manage disconnections in these settings. Design/methodology/approach The study employs a qualitative multiple-case study approach across four DSIs. While each case has a triadic analytical setting, the empirical material is collected through 21 interviews with Finnish industrial firms and technology providers. Findings The study identifies that structural holes in DSIs are multidimensional, extending beyond relational gaps to include knowledge, cognitive, technical, and temporal gaps. Industrial firms structure triadic relationships through brokerage practices, including streamlining workflows, balancing priorities, controlling the flow of information and access, and mediating customer knowledge across firm boundaries. These practices allow industrial firms to selectively preserve, reshape, and connect relationships across gap dimensions and project phases. Originality/value The study extends research on structural holes, brokerage, and digital service innovation. The findings move the discussion beyond the binary of connected vs. disconnected by showing that actors may become connected in one dimension while other gaps remain. The study further shows that industrial firms sustain brokerage in DSIs through a synthesis capability: they filter, translate, sequence, and align customer, technical, and business knowledge without necessarily owning all digital capabilities. Finally, the continued acceptance of brokerage depends on whether other actors perceive the industrial firm's intermediation as adding value through coordination, customer understanding, and technology integration.
Keywords: Digital service innovations; Supply network; Triad; Structural holes; Brokerage; Technology suppliers; Technology providers; Digital servitization; fi=Strateginen johtaminen|en=Strategic Management|